Overview of Physical and Chemical Factors in Fertilizer Companies - Ayu Nurjanah; Dhela Iskarina (Universitas Airlangga, 2021)
Introduction: Fertilizer companies are companies that use large amounts of chemicals, natural gas as raw equipment and assist in the production process, as well as the use of factory equipment with high temperatures and pressures, making companies with high levels of risk. The purpose of this study is to determine the general picture of physical and chemical factors in the work environment and the risks that can occur to workers and companies in fertilizer companies in Indonesia. Methods: This research was conducted using descriptive methods, the object observed in this study is the physical and chemical factors that exist in fertilizer companies. Results : Lighting intensity in all areas of the operational departments of fertilizer companies in Indonesia is only 12%, which is in accordance with the Threshold Limitation Value (TLV). Intensity of noise in the area of the company, as much as 17% is above the Threshold Limitation Value (TLV). The level of dust in this fertilizer company is 33% of the area that exceeds the Threshold Limitation Value (TLV). These three things can increase the risk to health, even increase the intelligence of the workers themselves. In addition to the risks to the workers, these three things can also benefit a company's productivity. Conclusion: All areas of fertilizer companies have risks originating from physical and chemical factors. So it needs to be carried out appropriate control in order to reduce the risks that can occur both for workers and companies.Keywords : dust, ferilizer plant, lighting, noise